Indigenous children's affective engagement with school: The influence of socio-structural, subjective and relational factors. (November 2017) - Dunstan, Laura; Hewitt, Belinda; Tomaszewski, Wojtek
In this study, Indigenous children's affective engagement with primary school is examined in terms of feelings of involvement and belonging at school and towards education as a worthwhile pursuit. Previous Australian research has concentrated on Indigenous children's education through attendance and school performance. Data from wave 6 of the Longitudinal Study of Indigenous Children are used to investigate the socio-structural, subjective and relational factors which influence affective engagement with school. Results show that good relationships with peers and teachers are positively associated with Indigenous children's affective engagement. Negative feelings about Indigenous identity are negatively associated with affective engagement. Socio-structural factors associated with higher affective engagement include being female, living in remote areas and being healthier. Results also show that parental education, employment, household income or area-level socio-economic circumstances are not associated with affective engagement. These results suggest that factors influencing Indigenous children's affective engagement with school and towards education may differ from those affecting school attendance. They also emphasise the importance of subjective and relational influences on improving Indigenous children's education outcomes.